Agricultural Implications of the Fukushima Nuclear Accident 2016
DOI: 10.1007/978-4-431-55828-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Monitoring of Radiocesium Redistribution Dynamics in a Forested Catchment in Fukushima After the Nuclear Power Plant Accident in March 2011

Abstract: The accident at the Fukushima Daiichi Nuclear Power Plant in March 2011 emitted 1.2 Â 10 16 Bq of cesium-137 ( 137 Cs) into the surrounding environment. Radioactive substances, including 137 Cs, were deposited onto forested areas in the northeastern region of Japan. 137 Cs is easily adsorbed onto clay minerals in the soil; thus, a major portion of 137 Cs can be transported as eroding soil and particulate organic matter in water discharge. Dissolved 137 Cs can be taken up by microbes, algae, and plants in soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Meanwhile, some of the 137 Cs that was deposited on fallen leaves and the like on the forest floor was absorbed through roots before being transferred to new leaves. The 137 Cs concentration exceeded 10,000 Bq kg -1 in most bark samples from jolcham oak during the same period in 2012 11) . The marginal difference in concentration between the sapwood and the heartwood of Japanese cedar as compared to jolcham oak in both 2012 and 2013 (Figure 2) indicates a much faster translocation of radioactive cesium in a tree trunk of Japanese cedar.…”
Section: Cs Concentration In Plantsmentioning
confidence: 85%
See 2 more Smart Citations
“…Meanwhile, some of the 137 Cs that was deposited on fallen leaves and the like on the forest floor was absorbed through roots before being transferred to new leaves. The 137 Cs concentration exceeded 10,000 Bq kg -1 in most bark samples from jolcham oak during the same period in 2012 11) . The marginal difference in concentration between the sapwood and the heartwood of Japanese cedar as compared to jolcham oak in both 2012 and 2013 (Figure 2) indicates a much faster translocation of radioactive cesium in a tree trunk of Japanese cedar.…”
Section: Cs Concentration In Plantsmentioning
confidence: 85%
“…Moreover, standing trees in the main forest were cut down and sampled in November of both 2012 and 2013 to estimate the amount of radioactive cesium buildup above the ground. The samples were divided into live leaves, branches, and trunks (bark, sapwood, and heartwood) to measure the radioactive cesium concentration 10,11) .…”
Section: Survey Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our four-year monitoring study since early 2012 at a forested headwater catchment in the northern part of Fukushima have demonstrated that radiocesium movement has been most drastic during the early years after the accident (Ohte et al 2013(Ohte et al , 2016. Observed results have shown that radiocesium has continuously moved from the forest canopies to the forest floor with throughfall, stemflow and litter fall (Endo et al 2015).…”
Section: Introductionmentioning
confidence: 82%
“…Therefore, citizens who are interested in practical results from this research will meet difficulties in access. Some other successful studies trying to monitor the level of radioactive contamination along with its impact on many of the aspects of life can be considered, for instance, Stein (2017) had monitored the status of beef [5], Ohte et al (2016) was concerned about movement of radiocesium in a forested catchment, Matsuda et. al.…”
Section: Introductionmentioning
confidence: 99%